Erythropoietin reduces nerve demyelination, neuropathic pain behavior and microglial MAPKs activation through erythropoietin receptors on Schwann cells in a rat model of peripheral neuropathy - Huang, Chun‐Ta; Chen, Seu‐Hwa; Lin, Shih‐Chang; Chen, Wei‐Ting; Lue, June‐Horng; Tsai, Yi‐Ju (Glia, 2018)
Neuroprotective effects of erythropoietin (EPO) on peripheral nerve injury remain uncertain. This study investigated the efficacy of EPO in attenuating median nerve chronic constriction injury (CCI)‐induced neuropathy. Animals received an intraneural injection of EPO at doses of 1,000, 3,000, or 5,000 units/kg 15 min before median nerve CCI. Afterwards, the behavioral and electrophysiological tests were conducted. Immunohistochemistry and immunoblotting were used for qualitative and quantitative analysis of microglial and mitogen‐activated protein kinases (MAPKs), including p38, JNK, and ERK, activation. Enzyme‐linked immunosorbent assay and microdialysis were applied to measure pro‐inflammatory cytokine and glutamate responses, respectively. EPO pre‐treatment dose‐dependently ameliorated neuropathic pain behavior, decreased microglial and MAPKs activation, and diminished the release of pro‐inflammatory cytokines and glutamate in the ipsilateral cuneate nucleus after CCI. Moreover, EPO pre‐treatment preserved myelination of the injured median nerve on morphological investigation and suppressed injury‐induced discharges. We also observed that EPO receptor (EPOR) expression was up‐regulated in the injured nerve after CCI. Double immunofluorescence showed that EPOR was localized to Schwann cells. Furthermore, siRNA‐mediated knockdown of EPOR expression eliminated the therapeutic effects of EPO on attenuating the microglial and MAPKs activation, pro‐inflammatory cytokine responses, injury discharges, and neuropathic pain behavior in CCI rats. In conclusion, binding of EPO to its receptors on Schwann cells maintains myelin integrity and blocks ectopic discharges in the injured median nerve, that in the end contribute to attenuation of neuropathic pain via reducing glutamate release from primary afferents and inhibiting activation of microglial MAPKs and production of pro‐inflammatory cytokines. Main Points Erythropoietin, via binding to its receptors on Schwann cells, preserved myelin integrity, attenuated ectopic discharges and eventually improved neuropathic pain in peripheral nerve injury